Grisel Syndrome: Prompt Diagnosis, Prompt Management Equals Happy Ending - Lim, Aidi Aswadi Halim; Abdul Aziz, Azian; Md Ralib, Ahmad Razali (IIUM Medical Journal Malaysia, 2018)
Grisel syndrome is a rare cause of torticollis resulting from subluxation of the atlanto-axial joint (C1-C2 vertebra) joint from surrounding soft tissue inflammation. Atlanto-axial joint injuries typically occur in the setting of trauma. However, here we report a case of a non-traumatic cause of atlanto-axial joint subluxation in a child. The child initially presented to our centre with 5 days history of torticollis preceded by a few days of upper respiratory tract symptoms. The initial radiograph of the cervical spine did not demonstrate any obvious abnormality. However, due to a high index of suspicion by the attending physician, a CT of the cervical spine was performed, which indeed revealed an atlanto-axial subluxation. The patient was put on cervical traction for a few days, and discharged well with soft collar and analgesia.